1998
DOI: 10.1093/ajcp/110.3.341
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Detection of Malignant Lymphoma in Cerebrospinal Fluid by Multiparameter Flow Cytometry

Abstract: A b s t r a c t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
52
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 5 publications
7
52
1
1
Order By: Relevance
“…In this sense, 'double negative' flow cytometry and cytological findings suggest that other nonmalignant conditions are responsible for the patient's CNS symptoms. We and others have previously obtained similar findings in patients with acute leukaemia [9,13] and NHL [10,11] but, to the best of our knowledge, this is the first report of a study involving a large number of HIV-positive patients. Parenchymal cerebral masses with deep locations do not seed malignant cells into the subarachnoid space, and this might explain the negative results of the cytological and flow cytometry analyses in some cases [15,16].…”
Section: Discussionsupporting
confidence: 77%
“…In this sense, 'double negative' flow cytometry and cytological findings suggest that other nonmalignant conditions are responsible for the patient's CNS symptoms. We and others have previously obtained similar findings in patients with acute leukaemia [9,13] and NHL [10,11] but, to the best of our knowledge, this is the first report of a study involving a large number of HIV-positive patients. Parenchymal cerebral masses with deep locations do not seed malignant cells into the subarachnoid space, and this might explain the negative results of the cytological and flow cytometry analyses in some cases [15,16].…”
Section: Discussionsupporting
confidence: 77%
“…2 Diagnosis of CNSi in CLL may be difficult because of the low burden of CLL cells in CSF, raising the issue of false positivity. However, the diagnosis of CNSi with a low percentage of malignant cells in CSF examination has previously been reported [12][13][14] and our patients were all symptomatic. Infectious investigation was negative.…”
mentioning
confidence: 57%
“…Both patients with brain mass had near normalization of neuroimaging. Since ibrutinib initiation, 1 patient has died in neurologic CR at 9 months and 3 are alive in CR after a median of 9 months (range, [8][9][10][11][12][13][14]. None of them needed additional treatment, for neither hematologic nor neurologic disease.…”
mentioning
confidence: 99%
“…10,42,45,46 Early studies analyzing non-stabilized CSF samples by ≤4-color FCM already demonstrated increased sensitivity in between 3% and 20% of cases as compared with cytology (Table 2). 42,[47][48][49][50] More recent analyses of larger series of CSF-stabilized samples using 4-8 color FCM have confirmed the greater sensitivity of FCM vs. CC with a median proportion of occult CNSL (FCM+/CC-CSF) of 12% (range: 5%-13%) ( Table 1). 10,45,51 Patients with occult CNSL (i.e., CC-and FCM+ CSF) typically showed lower levels of CSF infiltration (<20% or <1 tumor B cell/μL) than FCM+/CC+ cases, 45 further supporting the greater sensitivity of FCM vs. CC.…”
Section: Multiparameter Flow Cytometry Analysis Of Csf Samplesmentioning
confidence: 88%